IMPLIKASI PEDAGOGIS DALAM AL-QURAN SURAT ADZ-DZARIAT AYAT 56 DAN AL-BAQARAH AYAT 30 - cucun kindarasa cucun (TEXTURA, 2021)
Understanding the meaning of Islamic education in the Koran means having to analyze pedagogically a major aspect of the Koran as a guide for Muslims which has educational implications that are able to guide and direct humans to become believers, Muslims, muhsin, and muttakin. according to the purpose of human creation itself through a step-by-step process. As a source of guidance for Muslims, the Qur'an contains and carries values ​​that civilize humans. Nearly two-thirds of the verses of the Qur'an contain educational motivations for mankind. If we look closely at how God educates this world, it will appear that Allah as the Most Educator (al-murabbi ala'dham) with His nature and iradat has modeled a suprasystem. The purpose of this study is to determine the pedagogical implications contained in the letter Adz-Dzariat 56 and Al-Baqarah verse 30. This research is a library research (library reaserch). Where the data is obtained from library sources in the form of books related to the subject of research, the research data is collected using the documentation method. Literature review is carried out to explore concepts, theories, data from various existing literature sources and then used as a framework in seeing and assessing the objective conditions of various problems that occur in the field. The Qur'anic concept of human beings as the goal of Islamic education illustrates how Islamic ideology also adds to planning in preparation for life in this world and in the hereafter. Islamic education seeks to implement the principles of the Qur'an or in the sense of preparation for life in the hereafter without forgetting life in the world. The analysis of this third point, however, has led to another necessity that must be carried out in an effort to achieve humanitarian goals, namely the orientation of Islamic education.